Nonlinear energy-based control method for aircraft automatic landing systems - Akmeliawati, Rini; Mareels, Iven M. Y. (IEEE, 2010)
In this paper we present an aircraft automatic landing system using the nonlinear energy-based control method (NEM). This technique is based on aircraft energy management. NEM is based on the passivity-based control technique (PBC) and similar to Total Energy Control Systems (TECS). A physical interpretation of the NEM controller for the system is presented. We demonstrate that NEM provides insight into aircraft modeling and control while it achieves a satisfactory automatic flight control system (AFCS). The aircraft dynamics are presented via the energy functions. By modifying these functions, stabilization and tracking can be achieved. The automatic landing system is designed for a twin-engine civil aircraft, developed by the Group for Aeronautical Research and Technology in Europe (GARTEUR). Singular perturbation ideas are used to deal with the separation of the short-period and the phugoid dynamics. The proposed control laws appear to behave well even under extreme flight conditions.